Мікротопоніміка села Обложки на Глухівщині - Чернякова, Я.В. (Сіверщина в історії України, 2021)
У статті зафіксовано сучасну мікротопоніміку села Обложки
на Глухівщині, визначено структурно-семантичні та географічні
особливості назв цього населеного пункту.
Необхідною умовою освоєння людиною навколишнього світу є
його категоризація та номіналізація. Процес найменування, закріплення індивідуальних назв за конкретними, релевантними для
соціуму об’єктами зовнішнього світу відображає соціально-політичні, матеріально-господарські та духовно-культурні особливості розвитку цього суспільства. The article examines the microtoponymy of the village of Oblozhky,
characterizes the history of its formation, identifies structural, semantic
and geographical features of the names of settlements. A necessary
condition for human development of the world is its categorization and
nominalization. The process of naming, fixing individual names for specifi
c, relevant to society objects of the external world, reflects the socio-
political, material and economic and spiritual and cultural features
of the development of this society. Historical materials on microtoponymy
of Ukraine have not been published yet. To date, microtoponymy
of only certain regions of Ukraine has been studied. Research has long
been considered an urgent and top priority. This article is devoted to
the study of microtoponyms of Hlukhiv district of Sumy region, in particular,
the names of micro-objects of the village of Oblozhky became
the object of exploration. Microtoponyms of Hlukhiv district have not
been studied at all.